The influence of values in sustainable consumption among millennials - Andreas Falke; Nadine Schröder; Claudia Hofmann (Journal of Business Economics, 2021)
Due to climate change and global warming, sustainable consumption—as one possible solution to these challenges—is becoming more and more relevant. One generation that is affected the most by these developments are the millennials. While more and more baby boomers are retiring, millennials are now transitioning from being in training to being full-time employed, which marks a big change in their lives and makes understanding their values and consumption behaviour more important for marketers. The goal of our study is to clarify which values influence the building of attitude of millennials, if this influence differs according to employment status, and how attitude affects purchase intention concerning sustainable goods. Building to the list of values by Kahle (1983), the theory of planned behaviour, and perceived consumer effectiveness, we construct a framework to understand how values and employment status of millennials interact with their purchasing intention. Our results show that, among others, the values, that play a role during purchase intention forming, differ depending on the employment status. We also find that millennials place high importance on being in control when purchasing sustainable goods. Advertising and product managers can use our results to better understand and target the audience of their products as they construct their marketing efforts with the values of the audience in mind. In particular, messages that comply with the notion of being in control should be considered in every communication channel. This way, they may increase the share of sustainable consumers.
Keywords: A13; C38; M31; 650; Sustainable consumption; List of values; Millennials; Theory of planned behaviour